Banana cultivar names and synonyms in Southeast Asia - Valmayor, R.V.; Jamaluddin, S.H.; Silayoi, B.; Kusumo, S.; Danh, L.D.; Pascua, O.C.; Espino, R.R.C.; International Network for the Improvement of Banana and Plantain (2000)
The Southeast Asia region harbours the greatest wealth of banana diversity, both in wild and cultivated forms. This includes some of the rarest varieties in the world. But how to classify them and even what to call them has always been a complicated issue. In many cases, the same varieties have been given different names in different areas and the likewise the same name has been given to different varieties. In September 1999 a landmark meeting of the curators of national banana germplasm collections took place in the Philippines. They resolved the names of nearly 300 banana varieties and agreed on a classification system, following that of Cheeseman and the International Code of Nomenclature for Cultivated Plants. This 24-page booklet provides the background on the nomenclature and classification of bananas in the region and the final listing of variety names and synonyms agreed at the meeting in Southeast Asia. An essential companion for collectors, curators, breeders and researchers around the world.